Analysis of maximum power point tracking (MPPT) for photovoltaic (PV) power in distributed generation (DG) in micro-grid system / Ameerul Aiman Jeman - Jeman, Ameerul Aiman (2021)
The research is related to the renewable energy which is solar. Nowadays, the global use of renewable energy is higher as compared to few years back. The increased usage of renewable energy has led to this research. Solar energy is chosen, and this renewable energy relates to the main grid with rating of 25 kV. Solar power is chosen because of the demand in the market nowadays. The solar farm is producing 2.5 MW by using SunPower SPR-305-WHT with 8200 photovoltaic (PV) solar panel (Nser = 50, Npar = 164) in order supply load at micro-grid during islanding situation. The main purpose of this research is about the performance of load at micro-grid by varying the system parameters with Maximum Power Point Tracking (MPPT) applied into photovoltaic (PV) solar system. There is certain situation that will drop or increase the voltage based on current level of reactive power at micro-grid load and the improvised version of MPPT is proposed and introduced into the simulation for the system to optimize the output power from photovoltaic power generation. The process of MPPT functions by running a simulation on MATLAB software at ideal state. The contribution of this research will optimize the technique of MPPT. The superiority of the proposed non-linear controller is compared with the conventional Maximum Power Point Tracking (MPPT) controller and the computer analysis shows the elegance and effectiveness of this new control strategy. The effectiveness of both Maximum Power Point Tracking (MPPT) is shown to prove the title of this research.